Never smile at a monkey : and 17 other important things to remember - Jenkins, Steve, 1952- (Boston : Houghton Mifflin Books for Children, 2009)
Presents an illustrated discussion of what not to do around various dangerous animals, with warnings about petting a platypus, touching a tang fish, or pulling a python's tail.
Library Media Connection starred
School Library Journal starred
Wilson's Children
Booklist, October 2009
Bulletin (Center for Children's books), November 2009
Horn Book, April 2010
Keywords: Dangerous animals -- Juvenile literature; Dangerous animals; Dangerous animals